Tinjauan Hukum Konsep Hak Menguasai Negara Dalam Penetapan Kawasan Hutan - Ahmad Maulana Anha; Eman Solaiman (Alauddin Law Development Journal (ALDEV), 2022)
Article 570 of the Civil Code, which is still in use today, also states that "property right is the right to enjoy the use of something material freely, and to act freely on that material with full sovereignty". Other norms also emphasize ownership rights over land, as stipulated in article 571 of the Civil Code which reads "title to a plot of land contains ownership of everything on it and in the land". Seeing the above legal rules clearly reinforce the legal protection of the civil rights of the Indonesian people, especially for the Pattapang people who cannot be contested over lands that have been cultivated and controlled for generations, which have the status of ownership rights and are unilaterally claimed in SK 434 of stipulating forest areas in urban villages. Pattapang, Tinggimoncong District, Gowa Regency. This research was conducted to find out how the concept of the law of the right to control the State in the decree of forest area determination No. 434 in the Patappang village, Kab.gowa district. To minimize some of the legal problems that exist in the process of implementing the State's Right to Control in determining the location of forest areas, it is necessary to pay attention to the rights of the people living in the vicinity of the forest area to involve the community in the discussion process up to the determination of the location of the forest area. So that the principle of openness and even more so, the principle of democracy becomes part of every rule to be established. If indeed the State and its apparatus continue to make similar mistakes, seize people's living space on the pretext of rules and public interests, and do not care about the lives of their people, then it is necessary to ignore what they call rules and return to activities such as ordinary but not forgetting to prepare for resistance if at any time the State re-criminalizes the community. In the word of Allah S.W.T in surah Ar-Ra'd verse 11 it reads. Verily, Allah will not change the condition of a people before they change their own condition.